Genomic and Transcriptomic Analysis of Bovine Pasteurella multocida Serogroup A Strain Reveals Insights Into Virulence Attenuation - Zhan, Li; Zhang, Jiaqi; Zhao, Boyu; Li, Xintian; Zhang, Xiqing; Hu, Renge; Elken, Emad Mohammed; Kong, Lingcong; Gao, Yunhang (Frontiers in Veterinary Science, 2021)
Pasteurella multocida is one of the primary pathogens of bovine respiratory disease (BRD), with a huge losses in the cattle industry. The Pm3 strain was a natural isolates, which is strong pathogen and sensitive to fluoroquinolones antibiotics. A high fluoroquinolone resistant strain Pm64 (MIC=64 μg/mL) was formed after continuous induction with subinhibitory concentration (1/2MIC) of enrofloxacin，with the enhanced growth characteristics and large attenuation of pathogenicity in mice. This study reports the whole genome sequence and the transcription profile by RNA-Seq of strain Pm3/Pm64. The results showed that there was ineffective difference between the two strains at the genome level, 24 and 8 genes could be recognized added and lost in the gene islands (GIs) of Pm64. Those genes are involved in DNA binding, trehalose metabolism, material transportation, capsule synthesis, prophage, amino acid metabolism and other functions. 558 up-regulated and 568 down-regulated genes were found in Pm3 strain compared to Pm64 strain, from which 20 virulence factor-related DEGs were screened. Genes which they were mainly differentially transcribed were associated with capsular polysaccharide (CPS), lipopolysaccharide (LPS), lipooligosaccharide (LOS), Iron utilization and biofilm composition. We speculated that the main mechanism of virulence attenuation after the formation of resistance of Pm64 comes from the change of the expression profile of these genes. This report elucidated the toxicity targets of P. multocida serogroup A which provide a fundamental information to the elucidating the pathogenic mechanism and to decease antimicrobial drugs resistance.